Development of Literacy Programs for Students in School Libraries in Indonesia - Subur Subur; Singgih Prasetya Aji; Samsu Somadayo; Heru Kurniawan (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The research aims to explain the development of literacy programs in school libraries in Indonesia. This research is field research with a phenomenological approach with research locations in 10 junior high school libraries in Indonesia. Data collection is carried out using interviews, observations and documentation. Data analysis with reduction, classification, and verification. The results of this study found that the development of literacy programs in school libraries was carried out through habituation and learning activities. Habituation activities are carried out by inviting students to carry out literacy activities based on writing, religion, digital, reading angles, literacy ambassadors, reading challenges, and awarding. While learning activities are carried out by holding a class literacy club, mandatory visits to the library, and procuring class making.